What is the role of global health and sustainable development in Swedish medical education? A qualitative study of key stakeholders’ perspectives - Lotta Velin; Pia Svensson; Tobias Alfvén; Anette Agardh (BMC Medical Education, 2023)
Abstract Background Global health and sustainable development have increasingly been recognised as important parts of medical education, yet education on these issues remains fragmented and scarce. In 2020, a bill to reform the national medical curricula across all Swedish medical schools was introduced, including a greater emphasis on global health and sustainable development. This study aimed to explore the perspectives of key stakeholders in medical education on the role of global health and sustainable development in Swedish medical education. Methods This was a qualitative study based on semi-structured interviews with 11 key stakeholders in medical education, broadly defined as faculty board members (dean and/or vice-deans for medical education) and/or programme chairs representing six universities. Data were analysed using qualitative content analyis (QCA). The study was conducted according to the Consolidated Criteria for Reporting Qualitative research (COREQ) guidelines. Results Stakeholders discussed the challenges and opportunities associated with the modification of medical education, which was seen as necessary modernisation to fit the changing societal perception of the role of medical doctors. The anchoring process of redesigning the curriculum and integrating global health and sustainable development was discussed, with emphasis on ownership and mandate and the role of teachers and students in the process. Finding a shared understanding of global health and sustainable development was perceived as a challenge, associated with resistance due to fear of curriculum overload. To overcome this, integrating global health and sustainable development with other topics and developing existing components of the curricula were seen as important. Additionally, it was stressed that fostering capacity building and developing infrastructure, including utilization of digital tools and collaborations, were essential to ensure successful implementation. Conclusions Medical institutions should prepare future doctors to respond to the needs of a globalised world, which include knowledge of global health and sustainable development. However, conceptual uncertainties and questions about ownership remain among key stakeholders in medical education. Yet, key stakeholders also highlight that the inclusion of global health and sustainable development in the new curricula represents multiple overarching educational opportunities that can bring about necessary improvement.